Numerical simulation of the flow rectification measures in the forebay of the pumping station - Arifjanov, Aybek (Acta hydrotechnica, 2025)
The kinematics of flow movement in the forebays of pumping stations significantly influence the efficiency of pump operation. This study addresses the issue of sediment accumulation caused by improper flow velocity distribution in the intake structures of pumping stations. Research was conducted at the water intake structure of Uzbekistan’s Dehqonobod pumping station, located in Quva district, Fergana region. The study involved analyzing hydrodynamic processes within the intake structure based on the principles of fluid motion, combining experimental approaches with simulations using the COMSOL Multiphysics software suite to develop a 3D structural model of the prototype intake structure. Additionally, numerical simulations were performed using the Newton-Raphson scheme and the realizable k-? turbulence model for comparative analysis and evaluation. To ensure proper flow velocity distribution, six vertical columns were arranged in a triangular pattern relative to the flow movement, with a spacing of 1 meter between them. This arrangement was proposed so as to enhance technical and economic efficiency. The results of the study demonstrated that the installation of vertical columns increased the flow velocity near the right and left walls of the forebay, achieving a variation in velocity distribution of up to 20%. Specific recommendations were developed to optimize the hydrodynamic conditions and improve the pumping station's operational efficiency.
Keywords: finite volume model; flow pattern; flow regulating columns; flow velocity; k-? model; model volumna tekočine; Navier–Stokes equations; Navier-Stokesove enačbe; pretočna hitrost; rectification scheme; rektifikacijska shema; stebri za uravnavanje pretoka; vzorec pretoka